RETRACTED: Testing Environmental Kuznets Curve in the USA: What Role Institutional Quality, Globalization, Energy Consumption, Financial Development, and Remittances can Play? New Evidence From Dynamic ARDL Simulations Approach - Khan, Muhammad Imran; Kamran Khan, Muhammad; Dagar, Vishal; Oryani, Bahareh; Akbar, Syeda Saba; Salem, Sultan; Dildar, Sayyad Mahejabin (Frontiers in Environmental Science, 2021)
This study intends to examine the validity of the Environmental Kuznets Curve (EKC) in the United States of America (USA), considering the vital role of macroeconomic variables, such as economic growth, institutional quality, globalization, energy consumption, financial development, urbanization, and remittance from 1985 to 2020. The impact of positive/negative shock in a regressor on CO2 emissions keeps other regressors unchanged, has been investigated using the novel dynamic stimulated autoregressive distributed lag (ARDL) model. The empirical findings revealed the positive impact of economic growth and negative impact of the square economic growth on environmental degradation in the short- and long term. It indicates the validity of the EKC hypothesis in the case of the USA. Moreover, financial development, energy consumption, globalization, remittances inflow, urbanization reduce the environmental quality. On the contrary, institutional quality improves the environmental quality by reducing CO2 emissions. The appropriate recommendations to design the inclusive economic-environment national energy policy were proposed. Keywords: Institutional quality; globalization, financial development, remittances inflow, economic growth